EFFECTS OF ?-CAROTENE AND VITAMIN - C ON BLOOD ELECTROLYTE LEVELS OF JUVENILE RAINBOW TROUT (ONCORHYNCHUS MYKISS W. 1792) UNDER HYPOXIC STRESS - Kelestemur, Guluzar Tuna (Agricultural Research Communication Centre, 2012)
In this study, the effect of dietary supplementation of beta-carotene and vitamin C on blood electrolytes (Na+, K+, Ca+2, Mg+2, Cl-) and pH of juvenile rainbow trouts under hypoxic stress (4.5 mg/l O2) was investigated. Three diets were prepared differing only in the type of supplementation as follows: Bc dietary group with 70 mg/kg beta-carotene, Aa dietary group with 250 mg/kg Vitamin C and control (C) dietary group with no beta-carotene and Vitamin C. Based on statistical evaluations, it was observed that serum Na+ level of Aa group was significantly higher than Bc and C groups (p<0.05) and the least serum Na+ level was found in C group. Serum K+ and Cl- levels of Aa and Bc groups were determined to be significantly higher than C group (p<0.05). Serum Ca+2 level of C group was determined to be significantly higher than the other groups (p<0.05) whereas serum Mg+2 level of C group was found to be significantly lower than other groups (p<0.05). Serum pH level was not statistically different among the groups (p>0.05).
Keywords: Rainbow trout; Vitamin C; beta-carotene; Blood electrolytes; Stress; Hypoxia